Applying Rational Framework in PT. Sejahtera’S Business Process to enhance Corporate Road Map, Decisions, Company Activities and Project Executions - Fajar, Dimas; Mangkusubroto, Kuntoro; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2012)
The study aims to applying rational framework of processes in the problem solving of PT. Sejahtera’s Partnership and Organization challenges. It also focuses to problem analysis of organizational problem which produce disharmony among consortium members. With that result, a SMART analysis can be done to select Solution for the current situation and evaluate potential problem analysis in the two best course of action which is suited to company roadmap and strategy. The company shall be recommended to implement a combination of rational process and partnership selection process to have maximum benefit on a project and not to fall into the same organizational problem such as in previous RFID project. Furthermore, the company should replace the previous partnership and create a new partnership with a fresh start of rational selection. Selecting a project shall be inseparable with selecting with the right partnership. A partnership shall be evaluated accordingly by the principle of best practice and evaluated in criteria of technical risks, commercial risk and other project criteria that were driven by company strategy which access based strategy, gain track new record and innovations, also avoid Red Ocean Arenas. The rational framework of processes not only revising company strategy in practical level, but the process has to be implemented in projects and activities. Keywords: Rational Framework, Decision Making, Problem Analysis, SMART analysis and Potential Problem Analysis